2022
DOI: 10.3389/fmicb.2022.990736
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of a novel chromosomal class C β-lactamase, LAQ-1, and comparative genomic analysis of a multidrug resistance plasmid in Lelliottia amnigena P13

Abstract: IntroductionLelliottia amnigena, a bacterium usually isolated from natural environments, may cause human infections and has been suggested to be naturally resistant to second- and third-generation cephalosporins.MethodsIn this study, we determined the whole-genome sequence of an isolate, L. Amnigena P13, isolated from animal farm sewage. On the basis of genome sequence analysis, susceptibility testing, molecular cloning, and enzyme kinetic parameter analysis, we identified a novel chromosome-encoded AmpC β-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…S2), sharing 99.3 % nucleotide and 99.5 % amino acid pairwise identity with the reference sequence (accession MZ497396). In agreement with [25], we found that bla LAQ-1 encoded by GFKo1 had the obligatory serine active site of the β-lactamase catalytic motif S–V–S–K (serine–valine–serine–lysine) at positions 83–86, the typical class C β-lactamase motif Y–A–N (tryptophan–alanine–asparagine) at positions 169–171, D/E (a peptide segment containing two dicarboxylic amino acids) at positions 236–238 and the conserved triad K–T–G (lysine–threonine–glycine) at positions 334–336 (Fig. S3).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…S2), sharing 99.3 % nucleotide and 99.5 % amino acid pairwise identity with the reference sequence (accession MZ497396). In agreement with [25], we found that bla LAQ-1 encoded by GFKo1 had the obligatory serine active site of the β-lactamase catalytic motif S–V–S–K (serine–valine–serine–lysine) at positions 83–86, the typical class C β-lactamase motif Y–A–N (tryptophan–alanine–asparagine) at positions 169–171, D/E (a peptide segment containing two dicarboxylic amino acids) at positions 236–238 and the conserved triad K–T–G (lysine–threonine–glycine) at positions 334–336 (Fig. S3).…”
Section: Resultssupporting
confidence: 89%
“…The Bla LAQ-1 sequence of L. amnigena P13 represents the reference for this chromosomally encoded AmpC β-lactamase [25]. Twelve other AmpC β-lactamases (ACT-12, ACT-22, BIL-1, CMY-2, CMY-20, LAT-1, CFE-1, YRC-1, MIR-1, MIR-23, ACT-6, ACT-10 [25]) were included in the analysis for comparative purposes; the accessions for the amino acid sequences of these proteins are given in parentheses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations